2020
DOI: 10.1007/s10570-020-03495-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of ZnO nanorods on cotton fabrics via microwave hydrothermal method: effect of size and shape of nanorods on superhydrophobic and UV-blocking properties

Abstract: In this present research, a novel microwave hydrothermal method was applied to cotton fabrics to develop a superhydrophobic surface by rapid synthesis of aligned ZnO nanorods on the surface of the cotton fabric. A two-step approach was used to grow the ZnO nanorods. Firstly, the cotton fabric was coated by a seed layer of ZnO nanocrystals, synthesized using the microwave-assisted sol gel method. Secondly, the ZnO nanorods were grown rapidly on the seeded cotton fabrics using the microwave hydrothermal method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…There are other studies on UV protection cotton fabrics, the UPF values in which are range from tens to hundreds. [62][63][64] Only from the perspective of UV protection, our research is at a high level.…”
Section: Uv Protection Propertymentioning
confidence: 99%
“…There are other studies on UV protection cotton fabrics, the UPF values in which are range from tens to hundreds. [62][63][64] Only from the perspective of UV protection, our research is at a high level.…”
Section: Uv Protection Propertymentioning
confidence: 99%
“…The idea to prepare superhydrophobic fabrics is to introduce low surface energy substances to reduce the surface tension of the fabric, and to generate nanoparticles on the surface of the fabric or etch them chemically or physically to construct a structure with a micro/ nano rough structure similar to the lotus leaf surface. Therefore, researchers have adopted different strategies, 2 for example, by chemical vapor deposition, 3 sol-gel coating 4,5 and other methods to introduce uorinating agents [8][9][10][11][12][13] and other low surface energy substances into the fabric, or using nanoparticle in situ growth, 14 chemical etching 15 or plasma etching 16,17 to endow the fabric surface with a micro/nano-level rough structure to achieve the superhydrophobic aim. However, the operations of these methods are complicated, or the reagent used is not environmentally friendly, and the prepared superhydrophobic material has poor stability, which seriously hinders practical application.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 ZnO as a wide band gap (3.37 eV) semiconductor material has great chemical stability and biocompatibility, and has high exciton binding energy (60 meV) at room temperature; most research studies chose to attach or grow nanomaterials on the fabric to endow or change the performance of the fabric. [11][12][13][14] For example, Irmak et al 15 reported the growth of ZnO nanowires in carbon bres and proved that ZnO nanowires signicantly improved the photocatalytic performance of carbon bres. Sha et al 16 successfully prepared single-crystalline wurtzite ZnO nanorods on carbon bers and experimental results showed an outstanding degradation of MB solution and good recyclability.…”
Section: Introductionmentioning
confidence: 99%